Footstrike angle cut-off values to classify footstrike pattern in runners. Issue 2 (4th March 2023) - Mo, Shiwei; Huang, Meizhen; Ng, Leo; Cheung, Roy T. H.
ABSTRACT: Footstrike angle (FSA) has been widely used to classify footstrike pattern (FSP). However, inconsistent FSA cut-off values were adopted in previous studies. This study aimed to validate the FSA cut-off values in runners. Stride index, the gold standard to determine FSP, and FSA were obtained when 15 experienced runners, 14 novice runners and 14 untrained individuals performed 3-min run on an instrumented treadmill at their preferred running speeds in habitual, rearfoot, midfoot and forefoot strike patterns. According to the receiver operating characteristic curve associated with the Youden index, the optimal FSA cut-off values were −0.8° (i.e., cut-off angle for forefoot strike) –7.4° (i.e., cut-off angle for rearfoot strike) for runners. We observed minor differences in the FSA cut-off values across runners with various running experience and a wider cut-off range for midfoot strikers when a modified strike index was utilized. This validation study established cut-off footstrike angles for runners' FSP classification.